2010
DOI: 10.1123/jab.26.3.256
|View full text |Cite
|
Sign up to set email alerts
|

Force Enhancement of Quadriceps Femoris in Vivo and Its Dependence on Stretch-Induced Muscle Architectural Changes

Abstract: The purpose of this study was to investigate if force enhancement (FE) in vivo is influenced by stretch-induced changes of muscle architecture. Therefore, 18 subjects performed maximum voluntary isometric (100° knee flexion angle) and isometric-eccentric-isometric stretch contractions (80°–100° ω = 60°s−1) whereby pennation angle and fascicle length of vastus lateralis was determined using ultrasonography. We found significant (2-way repeated ANOVA; α = 0.05) enhanced torque of 5–10% after stretch as well as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 43 publications
7
30
0
1
Order By: Relevance
“…Seiberl et al (2010) showed that after 20°o f stretch fascicle lengths of VL were the same as those obtained in a purely isometric reference contraction at the same knee flexion angle of 100°. This result agrees with observations on human tibialis anterior (Tilp et al, 2011).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Seiberl et al (2010) showed that after 20°o f stretch fascicle lengths of VL were the same as those obtained in a purely isometric reference contraction at the same knee flexion angle of 100°. This result agrees with observations on human tibialis anterior (Tilp et al, 2011).…”
Section: Discussionmentioning
confidence: 64%
“…Assuming that the mechanisms underlying RFE and AR are the same, inconsistent AR in QF muscle parts is likely not caused by an inability of QF to produce RFE, as RFE was clearly observed in this muscle group for MVC conditions Seiberl et al, 2010). However, the force enhancing effects of stretch might be hidden due to motor redundancies in QF and the possibility of maintaining a sub-maximal contraction level with multiple motor control strategies.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the course of these investigations RFE was confirmed for ankle plantar and dorsi flexors (Pinniger and Cresswell, 2007;Power et al, 2012c;Tilp et al, 2009Tilp et al, , 2011, knee extensors (Altenburg et al, 2008;Hahn et al, 2007;Power et al, 2013c;Seiberl et al, 2012Seiberl et al, , 2010Shim and Garner, 2012), and knee flexors (Shim and Garner, 2012). Except for observations presented by Hahn et al (2007), RFE of 4-15% above isometric reference was constantly reported (Table 1).…”
Section: Rfe In the Context Of Activation Level And Muscle Sizementioning
confidence: 64%
“…Residual force enhancement, upon reaching an isometric steady state, has been well characterized in reduced muscle preparations (Herzog et al, 2006;Hisey et al, 2009;Lee et al, 2007;Mehta and Herzog, 2008;Rassier and Herzog, 2002;Rassier and Pavlov, 2012) and in humans (Edman et al, 1982;Hahn et al, 2010;Lee and Herzog, 2002;Minozzo et al, 2013;Pinniger and Cresswell, 2007;Power et al, 2013b;Power et al, 2012b, c;Seiberl et al, 2010;Shim and Garner, 2012;Tilp et al, 2009). However, few investigations have characterized the force transient phase immediately following stretch to the isometric steady-state force level (Cavagna, 1993;Koppes et al, 2013;Kosterina et al, 2012;Pinniger et al, 2006), and we are not aware of this transient phase reported in humans.…”
Section: Introductionmentioning
confidence: 87%